Rd Sharma Xi 2020 2021 _volume 2 Solutions for Class 11 Science Maths Chapter 29 Limits are provided here with simple step-by-step explanations. These solutions for Limits are extremely popular among Class 11 Science students for Maths Limits Solutions come handy for quickly completing your homework and preparing for exams. All questions and answers from the Rd Sharma Xi 2020 2021 _volume 2 Book of Class 11 Science Maths Chapter 29 are provided here for you for free. You will also love the ad-free experience on Meritnationâ€™s Rd Sharma Xi 2020 2021 _volume 2 Solutions. All Rd Sharma Xi 2020 2021 _volume 2 Solutions for class Class 11 Science Maths are prepared by experts and are 100% accurate.

#### Question 1:

Show that $\underset{x\to 0}{\mathrm{lim}}\frac{x}{\left|x\right|}$ does not exist.

Left hand limit:

Right hand limit:

Left hand limit ≠ Right hand limit

#### Question 2:

Find k so that $\underset{x\to 2}{\mathrm{lim}}f\left(x\right)$ may exist, where $f\left(x\right)=\left\{\begin{array}{ll}2x+3,& x\le 2\\ x+k,& x>2\end{array}\right\.$

Now,  exists if the left hand limit is equal to the right hand limit.

⇒7 = 2 + k
k = 5

#### Question 3:

Show that does not exist.

#### Question 4:

Let f(x) be a function defined by
Show that does not exist.

#### Question 5:

Let Prove that does not exist.

#### Question 6:

Let . Prove that does not exist.

We have,

LHL of f(x) at x = 0

=

RHL of f(x) at x = 0

=

Clearly, $\underset{x\to {0}^{-}}{\mathrm{lim}}f\left(x\right)\ne \underset{x\to {0}^{+}}{\mathrm{lim}}f\left(x\right)$

Hence, does not exist.

#### Question 7:

Find , where

We have,

LHL of f(x) at x = 3

=

RHL of f(x) at x = 3

=

Clearly, $\underset{x\to {3}^{-}}{\mathrm{lim}}f\left(x\right)=\underset{x\to {3}^{+}}{\mathrm{lim}}f\left(x\right)=4$

If Find and .

(ii)

#### Question 9:

Find , if $f\left(x\right)=\left\{\begin{array}{ll}{x}^{2}-1,& x\le 1\\ -{x}^{2}-1,& x>1\end{array}\right\$

#### Question 10:

Evaluate , where $f\left(x\right)=\left\{\begin{array}{ll}\frac{\left|x\right|}{x},& x\ne 0\\ 0,& x=0\end{array}\right\$

#### Question 11:

Let a1, a2, ..., an be fixed real numbers such that
f(x) = (xa1) (xa2) ... (xan)
What is For a ≠ a1, a2, ..., an. Compute

Find

#### Question 13:

Evaluate the following one sided limits:

(i)

(ii)

(iii)

(iv)

(v)

(vi)

(vii)

(viii)

(ix)

(x)

(xi)

(i)

(ii)

(iii)

(iv)

(v)

(vi)

(vii)

(viii)

(ix)

(x)

(xi)

#### Question 14:

Show that does not exist.

Find:

(i)

(ii)

(iii)

#### Question 16:

Prove that for all aR. Also, prove that

Show that

#### Question 18:

Find Is it equal to

#### Question 19:

Find

We know:
$\underset{x\to \frac{5}{2}}{\mathrm{lim}}\left[x\right]=\underset{x\to {\frac{5}{2}}^{-}}{\mathrm{lim}}\left[x\right]=\underset{x\to {\frac{5}{2}}^{+}}{\mathrm{lim}}\left[x\right]$

$\therefore \underset{x\to \frac{5}{2}}{\mathrm{lim}}\left[x\right]=2$

#### Question 20:

Evaluate (if it exists), where $f\left(x\right)=\left\{\begin{array}{ll}x-\left[x\right],& x<2\\ 4,& x=2\\ 3x-5,& x>2\end{array}.\right\$

#### Question 21:

Show that does not exist.

= – (An oscillating number that oscillates between –1 and 1)

#### Question 22:

Let and if , find the value of k.

We have,

It is given that,

Hence, the value of k is 6.

#### Question 1:

$\underset{x\to 1}{\mathrm{lim}}\left(\frac{{x}^{2}+1}{x+1}\right)\phantom{\rule{0ex}{0ex}}=\frac{{1}^{2}+1}{1+1}\phantom{\rule{0ex}{0ex}}=1$

#### Question 2:

$\underset{x\to 0}{\mathrm{lim}}\left(\frac{2{x}^{2}+3x+4}{{x}^{2}+3x+2}\right)\phantom{\rule{0ex}{0ex}}=\frac{2×0+3×0+4}{0+3×0+2}\phantom{\rule{0ex}{0ex}}=\frac{4}{2}\phantom{\rule{0ex}{0ex}}=2$

#### Question 3:

$\underset{x\to 3}{\mathrm{lim}}\left[\frac{\sqrt{2x+3}}{x+3}\right]\phantom{\rule{0ex}{0ex}}=\frac{\sqrt{2×3+3}}{3+3}\phantom{\rule{0ex}{0ex}}=\frac{3}{6}\phantom{\rule{0ex}{0ex}}=\frac{1}{2}$

#### Question 4:

$\underset{x\to 1}{\mathrm{lim}}\left(\frac{\sqrt{x+8}}{\sqrt{x}}\right)\phantom{\rule{0ex}{0ex}}=\frac{\sqrt{1+8}}{1}\phantom{\rule{0ex}{0ex}}=3$

#### Question 5:

$\underset{x\to a}{\mathrm{lim}}\left(\frac{\sqrt{x}+\sqrt{a}}{x+a}\right)\phantom{\rule{0ex}{0ex}}=\frac{\sqrt{a}+\sqrt{a}}{a+a}\phantom{\rule{0ex}{0ex}}=\frac{2\sqrt{a}}{2a}\phantom{\rule{0ex}{0ex}}=\frac{1}{\sqrt{a}}$

#### Question 6:

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{1+{\left(x-1\right)}^{2}}{1+{x}^{2}}\right]\phantom{\rule{0ex}{0ex}}=\frac{1+{\left(1-1\right)}^{2}}{1+{1}^{2}}\phantom{\rule{0ex}{0ex}}=\frac{1}{2}$

#### Question 7:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{{x}^{2/3}-9}{x-27}\right]\phantom{\rule{0ex}{0ex}}=\frac{0-9}{0-27}\phantom{\rule{0ex}{0ex}}=\frac{1}{3}$

#### Question 8:

$\underset{x\to 0}{\mathrm{lim}}\left(9\right)\phantom{\rule{0ex}{0ex}}=9$

f(x) = 9 is a constant function.
Its value does not depend on x.

#### Question 9:

$\underset{x\to 2}{\mathrm{lim}}\left(3-x\right)\phantom{\rule{0ex}{0ex}}=3-2\phantom{\rule{0ex}{0ex}}=1$

#### Question 10:

$\underset{x\to -1}{\mathrm{lim}}\left(4{x}^{2}+2\right)\phantom{\rule{0ex}{0ex}}=4{\left(-1\right)}^{2}+2\phantom{\rule{0ex}{0ex}}=4+2\phantom{\rule{0ex}{0ex}}=6$

#### Question 11:

Evaluate the following limits:

$\underset{x\to -1}{\mathrm{lim}}\frac{{x}^{3}-3x+1}{x-1}$

$\underset{x\to -1}{\mathrm{lim}}\left(\frac{{x}^{3}-3x+1}{x-1}\right)\phantom{\rule{0ex}{0ex}}=\frac{{\left(-1\right)}^{3}-3\left(-1\right)+1}{-1-1}\phantom{\rule{0ex}{0ex}}=\frac{-1+3+1}{-2}\phantom{\rule{0ex}{0ex}}=\frac{-3}{2}$

#### Question 12:

$\underset{x\to 0}{\mathrm{lim}}\left(\frac{3x+1}{x+3}\right)\phantom{\rule{0ex}{0ex}}=\frac{3×0+1}{0+3}\phantom{\rule{0ex}{0ex}}=\frac{1}{3}$

#### Question 13:

$\underset{x\to 3}{\mathrm{lim}}\left(\frac{{x}^{2}-9}{x+2}\right)\phantom{\rule{0ex}{0ex}}=\frac{{3}^{2}-9}{3+2}\phantom{\rule{0ex}{0ex}}=\frac{9-9}{5}\phantom{\rule{0ex}{0ex}}=0$

#### Question 14:

$\underset{x\to 0}{\mathrm{lim}}\left(\frac{ax+b}{cx+d}\right)\phantom{\rule{0ex}{0ex}}=\frac{a×0+b}{c×0+d}\phantom{\rule{0ex}{0ex}}=\frac{b}{d}$

#### Question 14:

$\underset{x\to 2}{\mathrm{lim}}\left[\frac{x}{x-2}-\frac{4}{{x}^{2}-2x}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{x}{x-2}-\frac{4}{x\left(x-2\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{{x}^{2}-4}{x\left(x-2\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{\left(x-2\right)\left(x+2\right)}{x\left(x-2\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{\left(x+2\right)}{x}\right]\phantom{\rule{0ex}{0ex}}=\frac{2+2}{2}\phantom{\rule{0ex}{0ex}}=2$

#### Question 15:

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left({x}^{3}-1\right)-x\left({x}^{2}+x-2\right)}{\left({x}^{2}+x-2\right)\left({x}^{3}-1\right)}\right]\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}=\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left({x}^{3}-1\right)-{x}^{3}-{x}^{2}+2x}{\left({x}^{2}+x-2\right)\left({x}^{3}-1\right)}\right]\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}=\underset{x\to 1}{\mathrm{lim}}\left[\frac{-{x}^{2}+2x-1}{\left({x}^{2}+x-2\right)\left(x-1\right)\left({x}^{2}+x+1\right)}\right]\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}=\underset{x\to 1}{\mathrm{lim}}\left[\frac{-\left({x}^{2}-2x+1\right)}{\left({x}^{2}+x-2\right)\left(x-1\right)\left({x}^{2}+x+1\right)}\right]\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}=\underset{x\to 1}{\mathrm{lim}}\left[\frac{-{\left(x-1\right)}^{2}}{\left({x}^{2}+x-2\right)\left(x-1\right)\left({x}^{2}+x+1\right)}\right]\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}=\underset{x\to 1}{\mathrm{lim}}\left[\frac{-\left(x-1\right)}{\left({x}^{2}+2x-x-2\right)\left({x}^{2}+x+1\right)}\right]\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}=\underset{x\to 1}{\mathrm{lim}}\left[\frac{-\left(x-1\right)}{\left\{x\left(x+2\right)-1\left(x+2\right)\right\}\left({x}^{2}+x+1\right)}\right]\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}=\underset{x\to 1}{\mathrm{lim}}\left[\frac{-\left(x-1\right)}{\left(x-1\right)\left(x+2\right)\left({x}^{2}+x+1\right)}\right]\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}=\frac{-1}{\left(1+2\right)\left(1+1+1\right)}\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}=\frac{-1}{9}$

#### Question 16:

$\underset{x\to 3}{\mathrm{lim}}\left[\frac{1}{x-3}-\frac{2}{{x}^{2}-4x+3}\right]\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}=\underset{x\to 3}{\mathrm{lim}}\left[\frac{1}{x-3}-\frac{2}{{x}^{2}-3x-x+3}\right]\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}=\underset{x\to 3}{\mathrm{lim}}\left[\frac{1}{x-3}-\frac{2}{x\left(x-3\right)-1\left(x-3\right)}\right]\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}=\underset{x\to 3}{\mathrm{lim}}\left[\frac{1}{x-3}-\frac{2}{\left(x-1\right)\left(x-3\right)}\right]\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}=\underset{x\to 3}{\mathrm{lim}}\left[\frac{x-1-2}{\left(x-3\right)\left(x-1\right)}\right]\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}=\underset{x\to 3}{\mathrm{lim}}\left[\frac{1}{x-1}\right]\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}=\frac{1}{3-1}\phantom{\rule{0ex}{0ex}}=\frac{1}{2}$

#### Question 17:

$\underset{x\to 2}{\mathrm{lim}}\left[\frac{1}{x-2}-\frac{2}{{x}^{2}-2x}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{1}{x-2}-\frac{2}{x\left(x-2\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{x-2}{x\left(x-2\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{1}{x}\right]\phantom{\rule{0ex}{0ex}}=\frac{1}{2}$

#### Question 21:

$\underset{x\to 2}{\mathrm{lim}}\left[\frac{1}{x-2}-\frac{4}{{x}^{3}-2{x}^{2}}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{1}{x-2}-\frac{4}{{x}^{2}\left(x-2\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{{x}^{2}-4}{{x}^{2}\left(x-2\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{\left(x-2\right)\left(x+2\right)}{{x}^{2}\left(x-2\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{x+2}{{x}^{2}}\right]\phantom{\rule{0ex}{0ex}}=\frac{2+2}{{2}^{2}}\phantom{\rule{0ex}{0ex}}=1$

#### Question 22:

$\underset{x\to 3}{\mathrm{lim}}\left[\frac{1}{x-3}-\frac{3}{{x}^{2}-3x}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 3}{\mathrm{lim}}\left[\frac{1}{x-3}-\frac{3}{x\left(x-3\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 3}{\mathrm{lim}}\left[\frac{x-3}{x\left(x-3\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 3}{\mathrm{lim}}\left[\frac{1}{x}\right]\phantom{\rule{0ex}{0ex}}=\frac{1}{3}$

#### Question 23:

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{1}{x-1}-\frac{2}{{x}^{2}-1}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 1}{\mathrm{lim}}\left[\frac{1}{x-1}-\frac{2}{\left(x-1\right)\left(x+1\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 1}{\mathrm{lim}}\left[\frac{x+1-2}{\left(x-1\right)\left(x+1\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left(x-1\right)}{\left(x-1\right)\left(x+1\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 1}{\mathrm{lim}}\left[\frac{1}{x+1}\right]\phantom{\rule{0ex}{0ex}}=\frac{1}{1+1}\phantom{\rule{0ex}{0ex}}=\frac{1}{2}$

#### Question 24:

$\underset{x\to 3}{\mathrm{lim}}\left[\left({x}^{2}-9\right)\left\{\frac{1}{x+3}+\frac{1}{x-3}\right\}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 3}{\mathrm{lim}}\left[\left({x}^{2}-9\right)\left\{\frac{x-3+x+3}{\left(x+3\right)\left(x-3\right)}\right\}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 3}{\mathrm{lim}}\left[\left({x}^{2}-9\right)\left(\frac{2x}{{x}^{2}-9}\right)\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 3}{\mathrm{lim}}\left(2x\right)\phantom{\rule{0ex}{0ex}}=2×3\phantom{\rule{0ex}{0ex}}=6$

#### Question 25:

p(x) = x4 $-$ 3x3 + 2
p(1) = 1 $-$ 3 + 2
= 0
Now, $\left(x-1\right)$ is a factor of p(x).

q(x) = x3 $-$ 5x2 + 3x + 1
q(1) = 1 $-$ 5 + 3 + 1
= 0
is a factor of q(x).

$⇒\underset{x\to 1}{\mathrm{lim}}\left[\frac{{x}^{4}-3{x}^{3}+2}{{x}^{3}-5{x}^{2}+3x+1}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left(x-1\right)\left({x}^{3}-2{x}^{2}-2x-2\right)}{\left(x-1\right)\left({x}^{2}-4x-1\right)}\right]\phantom{\rule{0ex}{0ex}}=\frac{\left(1{\right)}^{3}-2{\left(1\right)}^{2}-2\left(1\right)-2}{{\left(1\right)}^{2}-4×1-1}\phantom{\rule{0ex}{0ex}}=\frac{1-2-2-2}{1-4-1}\phantom{\rule{0ex}{0ex}}=\frac{-5}{-4}\phantom{\rule{0ex}{0ex}}=\frac{5}{4}$

#### Question 26:

$\underset{x\to 2}{\mathrm{lim}}\left[\frac{{x}^{3}+3{x}^{2}-9x-2}{{x}^{3}-x-6}\right]$

It is of the form $\frac{0}{0}.$

Let p(x) = x3 + 3x2 $-$ 9x $-$ 2
p(2) = 8 + 12 $-$ 18 $-$ 2
= 0
Now, $\left(x-2\right)$ is a factor of p(x).

Let q(x) = x3 – x – 6
q(2) = 8 – 2 – 6
= 0
is a factor of q(x).

$⇒\underset{x\to 2}{\mathrm{lim}}\left[\frac{{x}^{3}+3{x}^{2}-9x-2}{{x}^{3}-x-6}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{\left(x-2\right)\left({x}^{2}+5x+1\right)}{\left(x-2\right)\left({x}^{2}+2x+3\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{{x}^{2}+5x+1}{{x}^{2}+2x+3}\right]\phantom{\rule{0ex}{0ex}}=\frac{\left(2{\right)}^{2}+5×2+1}{{\left(2\right)}^{2}+2×2+3}\phantom{\rule{0ex}{0ex}}=\frac{4+10+1}{4+4+3}\phantom{\rule{0ex}{0ex}}=\frac{15}{11}$

#### Question 29:

Let p(x) = x3 + x2 + 4x + 12
p(–2) = 0
Thus, x = –2 is the root of p(x).
Now, $\left(x+2\right)$ is a factor of p(x).

p(x) = x3 + x2 + 4x + 12
= (x + 2)(x2x + 6)

Let q(x) = x3 – 3x + 2
q$\left(-2\right)$ = $-$8 + 6 + 2
= 0
Thus, x = $-$2 is the root of q(x).
Now, $\left(x+2\right)$ is a factor of q(x).

q(x) = (x + 2)(x2 – 2x + 1)

$⇒\underset{x\to -2}{\mathrm{lim}}\left[\frac{{x}^{3}+{x}^{2}+4x+12}{{x}^{3}-3x+2}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to -2}{\mathrm{lim}}\left[\frac{\left(x+2\right)\left({x}^{2}-x+6\right)}{\left(x+2\right)\left({x}^{2}-2x+1\right)}\right]\phantom{\rule{0ex}{0ex}}=\frac{\left(–2{\right)}^{2}-\left(-2\right)+6}{{\left(-2\right)}^{2}-2\left(-2\right)+1}\phantom{\rule{0ex}{0ex}}=\frac{4+2+6}{4+4+1}\phantom{\rule{0ex}{0ex}}=\frac{12}{9}\phantom{\rule{0ex}{0ex}}=\frac{4}{3}$

#### Question 30:

Let p(x) = x3 + 3x2 $-$ 6x + 2
p(1) = 1 + 3 $-$ 6 + 2
= 0
Now, is a factor of p(x).

p(x) = (x $-$ 1)(x2 + 4x $-$ 2)

q(x) = x3 + 3x2 $-$ 3x + 2
q(1) = 1 + 3 $-$ 3 $-$ 1
= 0
is a factor of p(x).

$⇒\underset{x\to 1}{\mathrm{lim}}\left[\frac{{x}^{3}+3{x}^{2}-6x+2}{{x}^{3}+3{x}^{2}-3x-1}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left(x-1\right)\left({x}^{2}+4x-2\right)}{\left(x-1\right)\left({x}^{2}+4x+1\right)}\right]\phantom{\rule{0ex}{0ex}}=\frac{\left(1{\right)}^{2}+4×1-2}{{\left(1\right)}^{2}+4×1+1}\phantom{\rule{0ex}{0ex}}=\frac{1+4-2}{1+4+1}\phantom{\rule{0ex}{0ex}}=\frac{3}{6}\phantom{\rule{0ex}{0ex}}=\frac{1}{2}$

#### Question 31:

$\underset{x\to 2}{\mathrm{lim}}\left[\frac{1}{x-2}-\frac{2\left(2x-3\right)}{{x}^{3}-3{x}^{2}+2x}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{1}{x-2}-\frac{2\left(2x-3\right)}{x\left({x}^{2}-3x+2\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{1}{x-2}-\frac{-2\left(2x-3\right)}{x\left({x}^{2}-2x-x+2\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{1}{x-2}-\frac{2\left(2x-3\right)}{x\left\{x\left(x-2\right)-1\left(x-2\right)\right\}}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{1}{x-2}-\frac{2\left(2x-3\right)}{x\left(x-1\right)\left(x-2\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{x\left(x-1\right)-2\left(2x-3\right)}{x\left(x-1\right)\left(x+2\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{{x}^{2}-x-4x+6}{x\left(x-1\right)\left(x+2\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{{x}^{2}-5x+6}{x\left(x-1\right)\left(x+2\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{{x}^{2}-2x-3x+6}{x\left(x-1\right)\left(x-2\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{x\left(x-2\right)-3\left(x-2\right)}{x\left(x-1\right)\left(x-2\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 2}{\mathrm{lim}}\left[\frac{\left(x-3\right)\left(x-2\right)}{x\left(x-1\right)\left(x-2\right)}\right]\phantom{\rule{0ex}{0ex}}=\frac{2-3}{2\left(2-1\right)}\phantom{\rule{0ex}{0ex}}=-\frac{1}{2}$

#### Question 33:

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{x-2}{{x}^{2}-x}-\frac{1}{{x}^{3}-3{x}^{2}+2x}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 1}{\mathrm{lim}}\left[\frac{x-2}{x\left(x-1\right)}-\frac{1}{x\left({x}^{2}-3x+2\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 1}{\mathrm{lim}}\left[\frac{x-2}{x\left(x-1\right)}-\frac{1}{x\left({x}^{2}-2x-x+2\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 1}{\mathrm{lim}}\left[\frac{x-2}{x\left(x-1\right)}-\frac{1}{x\left\{x\left(x-2\right)-1\left(x-2\right)\right\}}\right]$
$=\underset{x\to 1}{\mathrm{lim}}\left[\frac{x-2}{x\left(x-1\right)}-\frac{1}{x\left(x-1\right)\left(x-2\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 1}{\mathrm{lim}}\left[\frac{{\left(x-2\right)}^{2}-1}{x\left(x-1\right)\left(x-2\right)}\right]\phantom{\rule{0ex}{0ex}}$

$=\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left(x-1\right)\left(x-3\right)}{x\left(x-1\right)\left(x-2\right)}\right]\phantom{\rule{0ex}{0ex}}=\frac{\left(1-3\right)}{1\left(1-2\right)}\phantom{\rule{0ex}{0ex}}=\frac{-2}{-1}\phantom{\rule{0ex}{0ex}}=2$

#### Question 34:

Evaluate the following limits:

$\underset{x\to 1}{\mathrm{lim}}\frac{{x}^{7}-2{x}^{5}+1}{{x}^{3}-3{x}^{2}+2}$

When x = 1, the expression $\frac{{x}^{7}-2{x}^{5}+1}{{x}^{3}-3{x}^{2}+2}$ assumes the form $\frac{0}{0}$. So, (x − 1) is a factor of numerator and denominator.

Using long division method, we get

${x}^{7}-2{x}^{5}+1=\left(x-1\right)\left({x}^{6}+{x}^{5}-{x}^{4}-{x}^{3}-{x}^{2}-x-1\right)$

and ${x}^{3}-3{x}^{2}+2=\left(x-1\right)\left({x}^{2}-2x-2\right)$

$\therefore \underset{x\to 1}{\mathrm{lim}}\frac{{x}^{7}-2{x}^{5}+1}{{x}^{3}-3{x}^{2}+2}\phantom{\rule{0ex}{0ex}}=\underset{x\to 1}{\mathrm{lim}}\frac{\left(x-1\right)\left({x}^{6}+{x}^{5}-{x}^{4}-{x}^{3}-{x}^{2}-x-1\right)}{\left(x-1\right)\left({x}^{2}-2x-2\right)}\phantom{\rule{0ex}{0ex}}=\underset{x\to 1}{\mathrm{lim}}\frac{{x}^{6}+{x}^{5}-{x}^{4}-{x}^{3}-{x}^{2}-x-1}{{x}^{2}-2x-2}\phantom{\rule{0ex}{0ex}}=\frac{1+1-1-1-1-1-1}{1-2-2}\phantom{\rule{0ex}{0ex}}=\frac{-3}{-3}\phantom{\rule{0ex}{0ex}}=1\phantom{\rule{0ex}{0ex}}$

#### Question 1:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{\sqrt{1+x+{x}^{2}}-1}{x}\right]$

When x = 0, the expression $\frac{\sqrt{1+x+{x}^{2}}-1}{x}$ takes the form $\frac{0}{0}$.
Rationalising the numerator:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{\left(\sqrt{1+x+{x}^{2}}-1\right)\left(\sqrt{1+x+{x}^{2}}+1\right)}{x\left(\sqrt{1+x+{x}^{2}}+1\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 0}{\mathrm{lim}}\left[\frac{1+x+{x}^{2}-1}{x\left(\sqrt{1+x+{x}^{2}}+1\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 0}{\mathrm{lim}}\left[\frac{x\left(1+x\right)}{x\left(\sqrt{1+x+{x}^{2}}+1\right)}\right]\phantom{\rule{0ex}{0ex}}=\frac{1+0}{\sqrt{1+0+0}+1}\phantom{\rule{0ex}{0ex}}=\frac{1}{2}$

#### Question 2:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{2x}{\sqrt{a+x}-\sqrt{a-x}}\right]$

When x = 0, then the expression $\frac{2x}{\sqrt{a+x}-\sqrt{a-x}}$ becomes $\frac{0}{0}$.

Rationalising the denominator:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{2x}{\left(\sqrt{a+x}-\sqrt{a-x}\right)}×\frac{\left(\sqrt{a+x}+\sqrt{a-x}\right)}{\left(\sqrt{a+x}+\sqrt{a-x}\right)}\right]$

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{\left(2x\right)\left(\sqrt{a+x}+\sqrt{a-x}\right)}{\left(a+x\right)-\left(a-x\right)}\right]$

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{2x\left(\sqrt{a+x}+\sqrt{a-x}\right)}{2x}\right]$

$\sqrt{a}+\sqrt{a}$
$2\sqrt{a}$

#### Question 3:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{\sqrt{{a}^{2}+{x}^{2}}-a}{{x}^{2}}\right]$

On putting x = 0 in the expression $\sqrt{{a}^{2}+{x}^{2}}-a$, it becomes $\frac{0}{0}.$
Rationalising the numerator:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{\left(\sqrt{{a}^{2}+{x}^{2}}-a\right)\left(\sqrt{{a}^{2}+{x}^{2}}+a\right)}{{x}^{2}\left(\sqrt{{a}^{2}+{x}^{2}}+a\right)}\right]$
â€‹
$\underset{x\to 0}{\mathrm{lim}}\left[\frac{{a}^{2}+{x}^{2}-{a}^{2}}{{x}^{2}\left(\sqrt{{a}^{2}+{x}^{2}}+a\right)}\right]$

$\frac{1}{\sqrt{{a}^{2}}+a}$

$\frac{1}{2a}$

#### Question 4:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{\sqrt{1+x}-\sqrt{1-x}}{2x}\right]$

It is of the form $\frac{0}{0}.$

Rationalising the numerator:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{\left(\sqrt{1+x}-\sqrt{1-x}\right)\left(\sqrt{1+x}+\sqrt{1-x}\right)}{2x\left(\sqrt{1+x}+\sqrt{1-x}\right)}\right]$

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{2x}{2x\left(\sqrt{1+x}+\sqrt{1-x}\right)}\right]$

$\frac{1}{\sqrt{1+0}+\sqrt{1-0}}$
$\frac{1}{2}$

#### Question 5:

$\underset{x\to 2}{\mathrm{lim}}\left[\frac{\sqrt{3-x}-1}{2-x}\right]$

It is of the form $\frac{0}{0}.$
Rationalising the numerator:

$=\underset{x\to 2}{\mathrm{lim}}\left[\frac{3-x-1}{\left(2-x\right)\left(\sqrt{3-x}+1\right)}\right]$

$=\underset{x\to 2}{\mathrm{lim}}\left[\frac{\left(2-x\right)}{\left(2-x\right)\left(\sqrt{3-x}+1\right)}\right]$

$=\frac{1}{\sqrt{3-2}+1}\phantom{\rule{0ex}{0ex}}=\frac{1}{1+1}\phantom{\rule{0ex}{0ex}}=\frac{1}{2}$

#### Question 6:

$\underset{x\to 3}{\mathrm{lim}}\left[\frac{x-3}{\sqrt{x-2}-\sqrt{4-x}}\right]$

It is of form $\frac{0}{0}.$

Rationalising the denominator:

$\underset{x\to 3}{\mathrm{lim}}\left[\frac{\left(x-3\right)\left(\sqrt{x-2}+\sqrt{4-x}\right)}{\left(\sqrt{x-2}-\sqrt{4-x}\right)\left(\sqrt{x-2}+\sqrt{4-x}\right)}\right]$

$\underset{x\to 3}{\mathrm{lim}}\left[\frac{\left(x-3\right)\left(\sqrt{x-2}+\sqrt{4-x}\right)}{\left(x-2\right)-\left(4-x\right)}\right]$

$\underset{x\to 3}{\mathrm{lim}}\left[\frac{\left(x-3\right)\left(\sqrt{x-2}+\sqrt{4-x}\right)}{2x-6}\right]$

$\underset{x\to 3}{\mathrm{lim}}\left[\frac{\left(x-3\right)\left(\sqrt{x-2}+\sqrt{4-x}\right)}{2\left(x-3\right)}\right]$

$\frac{\sqrt{3-2}+\sqrt{4-3}}{2}$

$\frac{\sqrt{1}+\sqrt{1}}{2}$
$\frac{2}{2}=1$

#### Question 7:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{x}{\sqrt{1+x}-\sqrt{1-x}}\right]$

It is of the form $\frac{0}{0}$.

Rationalising the denominator:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{x}{\left(\sqrt{1+x}-\sqrt{1-x}\right)}×\frac{\left(\sqrt{1+x}+\sqrt{1-x}\right)}{\left(\sqrt{1+x}+\sqrt{1-x}\right)}\right]$

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{x\left(\sqrt{1+x}+\sqrt{1-x}\right)}{\left(1+x\right)-\left(1-x\right)}\right]$

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{x\left(\sqrt{1+x}+\sqrt{1-x}\right)}{2x}\right]$

$\frac{\sqrt{1}+\sqrt{1}}{2}$

$\frac{2}{2}$
= 1

#### Question 8:

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\sqrt{5x-4}-\sqrt{x}}{x-1}\right]$

It is of the form $\frac{0}{0}.$
Rationalising the numerator:

$\underset{x\to 1}{\mathrm{lim}}\left[\left(\frac{\sqrt{5x-4}-\sqrt{x}}{x-1}\right)\left(\frac{\sqrt{5x-4}+\sqrt{x}}{\sqrt{5x-4}+\sqrt{x}}\right)\right]$

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{5x-4-x}{\left(x-1\right)\left(\sqrt{5x-4}+\sqrt{x}\right)}\right]$

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{4\left(x-1\right)}{\left(x-1\right)\left(\sqrt{5x-4}+\sqrt{x}\right)}\right]$

$\frac{4}{\sqrt{5-4}+\sqrt{1}}$

$\frac{4}{2}$

= 2

#### Question 9:

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{x-1}{\sqrt{{x}^{2}+3}-2}\right]$

It is of the form $\frac{0}{0}$.
Rationalising the denominator:

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left(x-1\right)\left(\sqrt{{x}^{2}+3}+2\right)}{\left(\sqrt{{x}^{2}+3}-2\right)\left(\sqrt{{x}^{2}+3}+2\right)}\right]$

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left(x-1\right)\left(\sqrt{{x}^{2}+3}+2\right)}{{x}^{2}+3-4}\right]$

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left(x-1\right)\left(\sqrt{{x}^{2}+3}+2\right)}{\left({x}^{2}-1\right)}\right]$

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left(x-1\right)\left(\sqrt{{x}^{2}+3}+2\right)}{\left(x-1\right)\left(x+1\right)}\right]$

=$\frac{\sqrt{1+3}+2}{1+1}$

$\frac{4}{2}$

= 2

#### Question 10:

$\underset{x\to 3}{\mathrm{lim}}\left[\frac{\sqrt{x+3}-\sqrt{16}}{{x}^{2}-9}\right]$

It is of the form $\frac{0}{0}$.
Rationalising the numerator:

$\underset{x\to 3}{\mathrm{lim}}\left[\frac{\left(\sqrt{x+3}-\sqrt{6}\right)\left(\sqrt{x+3}+\sqrt{6}\right)}{\left({x}^{2}-9\right)\left(\sqrt{x+3}+\sqrt{6}\right)}\right]$

$\underset{x\to 3}{\mathrm{lim}}\left[\frac{\left(x+3-6\right)}{\left(x-3\right)\left(x+3\right)\left(\sqrt{x+3}+\sqrt{6}\right)}\right]$

$\frac{1}{6×2\sqrt{6}}$

$\frac{1}{12\sqrt{6}}$

#### Question 11:

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\sqrt{5x-4}-\sqrt{x}}{{x}^{2}-1}\right]$

It is of the form $\frac{0}{0}$.
Rationalising the numerator:

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left(\sqrt{5x-4}-\sqrt{x}\right)\left(\sqrt{5x-4}+\sqrt{x}\right)}{\left(\sqrt{5x-4}+\sqrt{x}\right)\left({x}^{2}-1\right)}\right]$

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{5x-4-x}{\left(\sqrt{5x-4}+\sqrt{x}\right)\left(x-1\right)\left(x+1\right)}\right]$

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{4\left(x-1\right)}{\left(\sqrt{5x-4}+\sqrt{x}\right)\left(x-1\right)\left(x+1\right)}\right]$

$\frac{4}{\left(\sqrt{5-4}+\sqrt{1}\right)\left(1+1\right)}$

$\frac{4}{2×2}$

= 1

#### Question 12:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{\sqrt{1+x}-1}{x}\right]$

It is of the form $\frac{0}{0}$.
Rationalising the numerator:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{\left(\sqrt{1+x}-1\right)\left(\sqrt{1+x}+1\right)}{x\left(\sqrt{1+x}+1\right)}\right]$

=$\underset{x\to 0}{\mathrm{lim}}\left[\frac{1+x-1}{x\left(\sqrt{1+x}+1\right)}\right]$

$\frac{1}{\sqrt{1+0}+1}$

$\frac{1}{2}$

#### Question 13:

$\underset{x\to 2}{\mathrm{lim}}\left[\frac{\sqrt{{x}^{2}+1}-\sqrt{5}}{x-2}\right]$

It is of the form $\frac{0}{0}$.
Rationalising the numerator:

$\underset{x\to 2}{\mathrm{lim}}\left[\frac{\left(\sqrt{{x}^{2}+1}-\sqrt{5}\right)\left(\sqrt{{x}^{2}+1}+\sqrt{5}\right)}{\left(x-2\right)\left(\sqrt{{x}^{2}+1}+\sqrt{5}\right)}\right]$

$\underset{x\to 2}{\mathrm{lim}}\left[\frac{{x}^{2}+1-5}{\left(x-2\right)\left(\sqrt{{x}^{2}+1}+\sqrt{5}\right)}\right]$

$\underset{x\to 2}{\mathrm{lim}}\left[\frac{{x}^{2}-4}{\left(x-2\right)\left(\sqrt{{x}^{2}+1}+\sqrt{5}\right)}\right]$

$\underset{x\to 2}{\mathrm{lim}}\left[\frac{\left(x-2\right)\left(x+2\right)}{\left(x-2\right)\left(\sqrt{{x}^{2}+1}+\sqrt{5}\right)}\right]$

$\frac{4}{2\sqrt{5}}$

$\frac{2}{\sqrt{5}}$

#### Question 14:

$\underset{x\to 2}{\mathrm{lim}}\left[\frac{x-2}{\sqrt{x}-\sqrt{2}}\right]$

It is of the form $\frac{0}{0}$.

$\underset{x\to 2}{\mathrm{lim}}\left[\frac{{\left(\sqrt{x}\right)}^{2}-{\left(\sqrt{2}\right)}^{2}}{x-\sqrt{2}}\right]$

$\underset{x\to 2}{\mathrm{lim}}\left[\frac{\left(\sqrt{x}-\sqrt{2}\right)\left(\sqrt{x}+\sqrt{2}\right)}{\left(x-\sqrt{2}\right)}\right]$

$\sqrt{2}+\sqrt{2}$

$2\sqrt{2}$

#### Question 15:

$\underset{x\to 7}{\mathrm{lim}}\left[\frac{4-\sqrt{9+x}}{1-\sqrt{8-x}}\right]$

It is of the form $\frac{0}{0}$.
Rationalising the numerator and the denominator:

$\underset{x\to 7}{\mathrm{lim}}\left[\frac{16-\left(9+x\right)}{\left(4+\sqrt{9+x}\right)}×\frac{\left(1+\sqrt{8-x}\right)}{1-\left(8-x\right)}\right]$

$\underset{x\to 7}{\mathrm{lim}}\left[\frac{-1\left(-7+x\right)\left(1+\sqrt{8-x}\right)}{\left(4+\sqrt{9+x}\right)\left(-7+x\right)}\right]$

$\underset{x\to 7}{\mathrm{lim}}\left[\frac{-\left(1+\sqrt{8-x}\right)}{4+\sqrt{9+x}}\right]$

$-\left(\frac{1+\sqrt{8-7}}{4+\sqrt{9+7}}\right)$

$\frac{-2}{4+4}$

$\frac{-1}{4}$

#### Question 16:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{\sqrt{a+x}-\sqrt{a}}{x\sqrt{{a}^{2}+ax}}\right]$

It is of the form $\frac{0}{0}$.
Rationalising the numerator:

$\frac{1}{2a\sqrt{a}}$

#### Question 17:

$\underset{x\to 5}{\mathrm{lim}}\left[\frac{x-5}{\sqrt{6x-5}-\sqrt{4x+5}}\right]$

It is of the form $\frac{0}{0}$.
Rationalising the denominator:

$\underset{x\to 5}{\mathrm{lim}}\left[\frac{\left(x-5\right)\left(\sqrt{6x-5}+\sqrt{4x+5}\right)}{2\left(x-5\right)}\right]$

$\frac{\sqrt{6×5-5}+\sqrt{4×5+5}}{2}$

$\frac{5+5}{2}$

= 5

#### Question 18:

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\sqrt{5x-4}-\sqrt{x}}{{x}^{3}-1}\right]$

It is of the form $\frac{0}{0}$.
Rationalising the numerator:

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{5x-4-x}{\left(x-1\right)\left({x}^{2}+x+1\right)\left(\sqrt{5x-4}+\sqrt{x}\right)}\right]$

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{4\left(x-1\right)}{\left(x-1\right)\left({x}^{2}+x+1\right)\left(\sqrt{5x-4}+\sqrt{x}\right)}\right]$

$\frac{4}{3\left(1+1\right)}$

$\frac{2}{3}$

#### Question 19:

$\underset{x\to 2}{\mathrm{lim}}\left[\frac{\sqrt{1+4x}-\sqrt{5+2x}}{x-2}\right]$

It is of the from $\frac{0}{0}$.
Rationalising the numerator:

$\underset{x\to 2}{\mathrm{lim}}\left[\frac{\left(1+4x\right)-\left(5+2x\right)}{\left(x-2\right)\left(\sqrt{1+4x}+\sqrt{5+2x}\right)}\right]$

$\underset{x\to 2}{\mathrm{lim}}\left[\frac{2\left(x-2\right)}{\left(x-2\right)\left(\sqrt{1+4x}+\sqrt{5+2x}\right)}\right]$

$\frac{2}{\left(\sqrt{1+4×2}+\sqrt{5+2×2}\right)}$

$\frac{2}{3+3}$

$\frac{1}{3}$

#### Question 20:

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\sqrt{3+x}-\sqrt{5-x}}{{x}^{2}-1}\right]$

It is of the form $\frac{0}{0}$.
Rationalising the numerator:

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left(\sqrt{3+x}-\sqrt{5-x}\right)\left(\sqrt{3+x}+\sqrt{5-x}\right)}{\left(x-1\right)\left(x+1\right)\left(\sqrt{3+x}+\sqrt{5-x}\right)}\right]$

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left(3+x\right)-\left(5-x\right)}{\left(x-1\right)\left(x+1\right)\left\{\sqrt{3+x}+\sqrt{5-x}\right\}}\right]$

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{2\left(x-1\right)}{\left(x-1\right)\left(x+1\right)\left\{\sqrt{3+x}+\sqrt{5-x}\right\}}\right]$

$\frac{1}{4}$

#### Question 21:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{\sqrt{1+{x}^{2}}-\sqrt{1-{x}^{2}}}{x}\right]$

It is of the form $\frac{0}{0}$.
Rationalising the numerator:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{\left(\sqrt{1+{x}^{2}}-\sqrt{1-{x}^{2}}\right)\left(\sqrt{1+{x}^{2}}+\sqrt{1-{x}^{2}}\right)}{\left(\sqrt{1+{x}^{2}}+\sqrt{1-{x}^{2}}\right)x}\right]$

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{\left(1+{x}^{2}\right)-\left(1-{x}^{2}\right)}{x\left\{\sqrt{1+{x}^{2}}+\sqrt{1-{x}^{2}}\right\}}\right]$

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{2{x}^{2}}{x\left\{\sqrt{1+{x}^{2}}+\sqrt{1-{x}^{2}}\right\}}\right]$

$\frac{2×0}{\sqrt{1+0}+\sqrt{1-0}}$

= 0

#### Question 22:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{\sqrt{1+x+{x}^{2}}-\sqrt{x+1}}{2{x}^{2}}\right]$

It is of the form $\frac{0}{0}$.
Rationalising the numerator:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{\left(\sqrt{1+x+{x}^{2}}-\sqrt{x+1}\right)\left(\sqrt{1+x+{x}^{2}}+\sqrt{x+1}\right)}{\left(\sqrt{1+x+{x}^{2}}+\sqrt{x+1}\right)2{x}^{2}}\right]$

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{\left(1+x+{x}^{2}\right)-\left(x+1\right)}{\left(\sqrt{1+x+{x}^{2}}+\sqrt{x+1}\right)2{x}^{2}}\right]$

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{{x}^{2}}{\left(\sqrt{1+x+{x}^{2}}+\sqrt{x+1}\right)\left(2{x}^{2}\right)}\right]$

$\frac{1}{\left(\sqrt{1+0+0}+\sqrt{0+1}\right)×2}$

$\frac{1}{2}×\frac{1}{2}$

$\frac{1}{4}$

#### Question 23:

$\underset{x\to 4}{\mathrm{lim}}\left[\frac{2-\sqrt{x}}{4-x}\right]$

$\underset{x\to 4}{\mathrm{lim}}\left[\frac{2-\sqrt{x}}{2-{\left(\sqrt{x}\right)}^{2}}\right]$

$\underset{x\to 4}{\mathrm{lim}}\left[\frac{\left(2-\sqrt{x}\right)}{\left(2-\sqrt{x}\right)\left(2+\sqrt{x}\right)}\right]$

$\frac{1}{2+\sqrt{4}}$

$\frac{1}{2+2}$

$\frac{1}{4}$

#### Question 24:

$\underset{x\to a}{\mathrm{lim}}\left[\frac{x-a}{\sqrt{x}-\sqrt{a}}\right]$

$\underset{x\to a}{\mathrm{lim}}\left[\frac{{\left(\sqrt{x}\right)}^{2}-{a}^{2}}{\sqrt{x}-\sqrt{a}}\right]$

$\sqrt{a}+\sqrt{a}$

$2\sqrt{a}$

#### Question 25:

It is of the form $\frac{0}{0}$.

Rationalising the numerator:

#### Question 26:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{\sqrt{2-x}-\sqrt{2+x}}{x}\right]$

It is of the form $\frac{0}{0}$.
Rationalising the numerator:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{\left(\sqrt{2-x}-\sqrt{2+x}\right)\left(\sqrt{2-x}+\sqrt{2+x}\right)}{x\left(\sqrt{2-x}+\sqrt{2+x}\right)}\right]$

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{\left(2-x\right)-\left(2+x\right)}{x\left(\sqrt{2-x}+\sqrt{2+x}\right)}\right]$

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{-2x}{x\left(\sqrt{2-x}+\sqrt{2+x}\right)}\right]$

$\frac{-2}{2\sqrt{2}}$

$-\frac{1}{\sqrt{2}}$

#### Question 27:

It is of the form $\frac{0}{0}$.

Rationalising the numerator:

#### Question 28:

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left(2x-3\right)\left(\sqrt{x}-1\right)}{3{x}^{2}+3x-6}\right]$

It is of the form $\frac{0}{0}$.

⇒ $\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left(2x-3\right)\left(\sqrt{x}-1\right)}{3\left({x}^{2}+x-2\right)}\right]$

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left(2x-3\right)\left(\sqrt{x}-1\right)}{3\left({x}^{2}+2x-x-2\right)}\right]$

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left(2x-3\right)\left(\sqrt{x}-1\right)}{3\left(x\left(x+2\right)-1\left(x+2\right)\right)}\right]$

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left(2x-3\right)\left(\sqrt{x}-1\right)}{3\left(x-1\right)\left(x+2\right)}\right]$

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left(2x-3\right)\left(\sqrt{x}-1\right)}{3\left({\left(\sqrt{x}\right)}^{2}-{1}^{2}\right)\left(x+2\right)}\right]$

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left(2x-3\right)\left(\sqrt{x}-1\right)}{3\left(\sqrt{x}+1\right)\left(\sqrt{x}-1\right)\left(x+2\right)}\right]$

$\frac{-1}{3\left(2\right)×3}$

$\frac{-1}{18}$

#### Question 29:

It is of the form $\frac{0}{0}$.
Rationalising the numerator and the denominator:

#### Question 30:

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{{x}^{2}-\sqrt{x}}{\sqrt{x}-1}\right]$

It is of the form $\frac{0}{0}$.

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\sqrt{x}\left(x\sqrt{x}-1\right)}{\sqrt{x}-1}\right]$

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\sqrt{x}\left({x}^{3/2}-1\right)}{{x}^{\frac{1}{2}}-1}\right]$

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{\left(\sqrt{x}\right)\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)}{\left(\sqrt{x}-1\right)}\right]$

= 1 (1 + 1 + 1)

= 3

#### Question 31:

$\underset{h\to 0}{\mathrm{lim}}\left[\frac{\sqrt{x+h}-\sqrt{x}}{h}\right]$

It is of the form $\frac{0}{0}$.
Rationalising the numerator:
$\underset{h\to 0}{\mathrm{lim}}\left[\frac{\left(\sqrt{x+h}-\sqrt{x}\right)}{h}×\frac{\left(\sqrt{x+h}+\sqrt{x}\right)}{\left(\sqrt{x+h}+\sqrt{x}\right)}\right]$

$\underset{h\to 0}{\mathrm{lim}}\left[\frac{\left(x+h\right)-x}{h\left(\sqrt{x+h}+\sqrt{x}\right)}\right]$

$\frac{1}{\sqrt{x}+\sqrt{x}}$

$\frac{1}{2\sqrt{x}}$

#### Question 32:

$\underset{x\to \sqrt{10}}{\mathrm{lim}}\left[\frac{\sqrt{7+2x}-\left(\sqrt{5}+\sqrt{2}\right)}{{x}^{2}-{\left(\sqrt{10}\right)}^{2}}\right]$

$\underset{x\to \sqrt{10}}{\mathrm{lim}}\left[\frac{\sqrt{7+2x}-\sqrt{{\left(\sqrt{5}+\sqrt{2}\right)}^{2}}}{\left(x-\sqrt{10}\right)\left(x+\sqrt{10}\right)}\right]$

$\underset{x\to \sqrt{10}}{\mathrm{lim}}\left[\frac{\sqrt{7+2x}-\sqrt{5+2+2\sqrt{5}\sqrt{2}}}{\left(x-\sqrt{10}\right)\left(x+\sqrt{10}\right)}\right]$

$\underset{x\to \sqrt{10}}{\mathrm{lim}}\left[\frac{\sqrt{7+2x}-\sqrt{7+2\sqrt{10}}}{\left(x-\sqrt{10}\right)\left(x+\sqrt{10}\right)}\right]$

Rationalising the numerator:

$=\frac{2}{\left(2\sqrt{10}\right)×2\sqrt{7+2\sqrt{10}}}\phantom{\rule{0ex}{0ex}}=\frac{1}{2\sqrt{10}\sqrt{{\left(\sqrt{5}+\sqrt{2}\right)}^{2}}}$

$\frac{1}{2\sqrt{10}\left(\sqrt{5}+\sqrt{2}\right)}×\frac{\sqrt{5}-\sqrt{2}}{\sqrt{5}-\sqrt{2}}$

$=\frac{1}{2\sqrt{10}}\left[\frac{\sqrt{5}-\sqrt{2}}{{\left(\sqrt{5}\right)}^{2}-{\left(\sqrt{2}\right)}^{2}}\right]\phantom{\rule{0ex}{0ex}}$

$\frac{\sqrt{5}-\sqrt{2}}{6\sqrt{10}}$

#### Question 33:

$\underset{x\to \sqrt{6}}{\mathrm{lim}}\left[\frac{\sqrt{5+2x}-\left(\sqrt{3}+\sqrt{2}\right)}{{x}^{2}-6}\right]$

$\underset{x\to \sqrt{6}}{\mathrm{lim}}\left[\frac{\sqrt{5+2x}-\sqrt{{\left(\sqrt{3}+\sqrt{2}\right)}^{2}}}{{x}^{2}-{\left(\sqrt{6}\right)}^{2}}\right]$

$\underset{x\to \sqrt{6}}{\mathrm{lim}}\left[\frac{\sqrt{5+2x}-\sqrt{3+2+2\sqrt{6}}}{\left(x-\sqrt{6}\right)\left(x+\sqrt{6}\right)}\right]$

$\underset{x\to \sqrt{6}}{\mathrm{lim}}\left[\frac{\sqrt{5+2x}-\sqrt{5+2\sqrt{6}}}{\left(x-\sqrt{6}\right)\left(x+\sqrt{6}\right)}\right]$

Rationalising the numerator:

$\underset{x\to \sqrt{6}}{\mathrm{lim}}\left[\frac{\left(\sqrt{5+2x}-\sqrt{5+2\sqrt{6}}\right)\left(\sqrt{5+2x}+\sqrt{5+2\sqrt{6}}\right)}{\left(x-\sqrt{6}\right)\left(x+\sqrt{6}\right)\left(\sqrt{5+2x}+\sqrt{5+2\sqrt{6}}\right)}\right]$

$\underset{x\to \sqrt{6}}{\mathrm{lim}}\left[\frac{\left(5+2x\right)-\left(5+2\sqrt{6}\right)}{\left(x-\sqrt{6}\right)\left(x+\sqrt{6}\right)\left(\sqrt{5+2x}+\sqrt{5+2\sqrt{6}}\right)}\right]$

$\underset{x\to \sqrt{6}}{\mathrm{lim}}\left[\frac{2\left(x-\sqrt{6}\right)}{\left(x-\sqrt{6}\right)\left(x+\sqrt{6}\right)\left(\sqrt{5+2x}+\sqrt{5+2\sqrt{6}}\right)}\right]$

$\frac{2}{\left(\sqrt{6}+\sqrt{6}\right)\left(\sqrt{5+2\sqrt{6}}+\sqrt{5+2\sqrt{6}}\right)}$

$\frac{1}{2\sqrt{6}\left(\sqrt{{\left(\sqrt{3}+\sqrt{2}\right)}^{2}}\right)}$

$\frac{1}{2\sqrt{6}\left(\sqrt{3}+\sqrt{2}\right)}$

$\frac{1}{2\sqrt{6}\left(\sqrt{3}+\sqrt{2}\right)}×\frac{\left(\sqrt{3}-\sqrt{2}\right)}{\left(\sqrt{3}-\sqrt{2}\right)}$

$\frac{\sqrt{3}-\sqrt{2}}{2\sqrt{6}\left(3-2\right)}$

$\frac{\sqrt{3}-\sqrt{2}}{2\sqrt{6}}$

#### Question 34:

$\underset{x\to \sqrt{2}}{\mathrm{lim}}\left[\frac{\sqrt{3+2x}-\left(\sqrt{2}+1\right)}{{x}^{2}-2}\right]$

$\underset{x\to \sqrt{2}}{\mathrm{lim}}\left[\frac{\sqrt{3+2x}-\sqrt{{\left(\sqrt{2}+1\right)}^{2}}}{\left(x-\sqrt{2}\right)\left(x+\sqrt{2}\right)}\right]$

$\underset{x\to \sqrt{2}}{\mathrm{lim}}\left[\frac{\sqrt{3+2x}-\sqrt{2+1+2\sqrt{2}}}{\left(x-\sqrt{2}\right)\left(x+\sqrt{2}\right)}\right]$

$\underset{x\to \sqrt{2}}{\mathrm{lim}}\left[\frac{\left(\sqrt{3+2x}-\sqrt{3+2\sqrt{2}}\right)}{\left(x-\sqrt{2}\right)\left(x+\sqrt{2}\right)}\right]$

Rationalising the numerator:

$\underset{x\to \sqrt{2}}{\mathrm{lim}}\left[\frac{\left(\sqrt{3+2x}-\sqrt{3+2\sqrt{2}}\right)\left(\sqrt{3+2x}+\sqrt{3+2\sqrt{2}}\right)}{\left(x-\sqrt{2}\right)\left(x+\sqrt{2}\right)\left(\sqrt{3+2x}+\sqrt{3+2\sqrt{2}}\right)}\right]$

$\underset{x\to \sqrt{2}}{\mathrm{lim}}\left[\frac{\left(3+2x\right)-\left(3+2\sqrt{2}\right)}{\left(x-\sqrt{2}\right)\left(x+\sqrt{2}\right)\left(\sqrt{3+2x}+\sqrt{3+2\sqrt{2}}\right)}\right]$

$\underset{x\to \sqrt{2}}{\mathrm{lim}}\left[\frac{2\left(x-\sqrt{2}\right)}{\left(x-\sqrt{2}\right)\left(x+\sqrt{2}\right)\left(\sqrt{3+2x}+\sqrt{3+2\sqrt{2}}\right)}\right]$

$\frac{2}{\left(\sqrt{2}+\sqrt{2}\right)\left(\sqrt{3+2\sqrt{2}}+\sqrt{3+2\sqrt{2}}\right)}$

$\frac{2}{\left(2\sqrt{2}\right)\left(2\sqrt{3+2\sqrt{2}}\right)}$

$\frac{1}{2\sqrt{2}\left(\sqrt{3+2\sqrt{2}}\right)}$

$\frac{1}{2\sqrt{2}\sqrt{{\left(\sqrt{2}+1\right)}^{2}}}$

$\frac{1}{2\sqrt{2}\left(\sqrt{2}+1\right)}×\frac{\sqrt{2}-1}{\sqrt{2}-1}$

$\frac{\sqrt{2}-1}{2\sqrt{2}\left(2-1\right)}$

$\frac{\sqrt{2}-1}{2\sqrt{2}}$

#### Question 1:

Let y = x + 2 and b = a + 2.

When x → a, then x + 2 â€‹→ a + 2.
y â€‹→ b

$\underset{y\to b}{\mathrm{lim}}\left[\frac{{y}^{\frac{5}{2}}-{b}^{\frac{5}{2}}}{y-b}\right]\phantom{\rule{0ex}{0ex}}=\frac{5}{2}{\left(b\right)}^{\frac{5}{2}-1}\phantom{\rule{0ex}{0ex}}=\frac{5}{2}{b}^{\frac{3}{2}}\phantom{\rule{0ex}{0ex}}=\frac{5}{2}{\left(a+2\right)}^{\frac{3}{2}}$

#### Question 2:

Let y = x + 2 and b = a + 2.

When x â€‹→ a and x + 2 â€‹→ a + 2.
$⇒$y â€‹→ b

#### Question 3:

Let y = 1 + x

When x â€‹→ 0, then 1 + x → 1.
$⇒$y â€‹→ 1

$\underset{y\to 1}{\mathrm{lim}}\left[\left(\frac{{y}^{6}-{1}^{6}}{y-1}\right)×\frac{\left(y-1\right)}{{y}^{2}-{1}^{2}}\right]\phantom{\rule{0ex}{0ex}}=\frac{6×{\left(1\right)}^{6-1}}{2×{\left(1\right)}^{2-1}}\phantom{\rule{0ex}{0ex}}=\frac{6}{2}\phantom{\rule{0ex}{0ex}}=3$

Let y = 2x

#### Question 12:

If find the value of n.

x(3)n – 1 = 108
x(3)n – 1 = 4 × 33

On comparing LHS and RHS, we observe that x is equal to 4.

#### Question 13:

If find all possible values of a.

#### Question 14:

If find all possible values of a.

#### Question 15:

If find all possible values of a.

#### Question 16:

If find all possible values of a.

#### Question 4:

It is of the form ∞ - ∞.

Rationalising the numerator:

#### Question 5:

$\underset{x\to \infty }{\mathrm{lim}}\sqrt{x+1}-\sqrt{x}$

It is of the form ∞–â€‹â€‹∞.

On rationalising, we get:

#### Question 6:

$\underset{x\to \infty }{\mathrm{lim}}\sqrt{{x}^{2}+7x-x}$

#### Question 7:

$\underset{x\to \infty }{\mathrm{lim}}\frac{x}{\sqrt{4{x}^{2}+1}-1}$

#### Question 8:

$\underset{n\to \infty }{\mathrm{lim}}\frac{{n}^{2}}{1+2+3+...+n}$

#### Question 9:

$\underset{x\to \infty }{\mathrm{lim}}\frac{3{x}^{-1}+4{x}^{-2}}{5{x}^{-1}+6{x}^{-2}}$

#### Question 10:

$\underset{x\to \infty }{\mathrm{lim}}\frac{\sqrt{{x}^{2}+{a}^{2}}-\sqrt{{x}^{2}+{b}^{2}}}{\sqrt{{x}^{2}+{c}^{2}}-\sqrt{{x}^{2}+{d}^{2}}}$

#### Question 11:

$\underset{n\to \infty }{\mathrm{lim}}\left[\frac{\left(n+2\right)!+\left(n+1\right)!}{\left(n+2\right)!-\left(n+1\right)!}\right]$

Dividing the numerator and the denominator by n:

#### Question 12:

$\underset{x\to \infty }{\mathrm{lim}}\left[x\left\{\sqrt{{x}^{2}+1}-\sqrt{{x}^{2}-1}\right\}\right]$

#### Question 14:

$\underset{n\to \infty }{\mathrm{lim}}\left[\frac{{1}^{2}+{2}^{2}+...+{n}^{2}}{{n}^{3}}\right]$

#### Question 15:

$\underset{n\to \infty }{\mathrm{lim}}\left[\frac{1+2+3......n-1}{{n}^{2}}\right]$

#### Question 16:

$\underset{n\to \infty }{\mathrm{lim}}\left[\frac{{1}^{3}+{2}^{3}+....{n}^{3}}{{n}^{4}}\right]$

#### Question 17:

$\underset{n\to \infty }{\mathrm{lim}}\left[\frac{{1}^{3}+{2}^{3}+...{n}^{3}}{{\left(n-1\right)}^{4}}\right]$

Dividing the numerator and the denominator by n4:

#### Question 18:

$\underset{x\to \infty }{\mathrm{lim}}\left[\sqrt{x}\left\{\sqrt{x+1}-\sqrt{x}\right\}\right]$

Dividing the numerator and the denominator by $\sqrt{x}$:

#### Question 19:

$\underset{n\to \infty }{\mathrm{lim}}\left[\frac{1}{3}+\frac{1}{{3}^{2}}+\frac{1}{{3}^{3}}+...+\frac{1}{{3}^{n}}\right]$

#### Question 20:

$\underset{x\to \infty }{\mathrm{lim}}\left[\frac{{x}^{4}+7{x}^{3}+46x+a}{{x}^{4}+6}\right]$, where a is a non-zero real number.

$\underset{x\to \infty }{\mathrm{lim}}\left[\frac{{x}^{4}+7{x}^{3}+46x+a}{{x}^{4}+6}\right]$

Dividing the numerator and the denominator by x4:

#### Question 21:

and $\underset{x\to \infty }{\mathrm{lim}}f\left(x\right)=1,$ then prove that f(−2) = f(2) = 1

Dividing the numerator and the denominator by x2:

#### Question 22:

Show that $\underset{x\to \infty }{\mathrm{lim}}\left(\sqrt{{x}^{2}+x+1}-x\right)\ne \underset{x\to \infty }{\mathrm{lim}}\left(\sqrt{{x}^{2}+1}-x\right)$

Rationalising the numerator:

#### Question 23:

$\underset{x\to -\infty }{\mathrm{lim}}\left(\sqrt{4{x}^{2}-7x}+2x\right)$

$\underset{x\to -\infty }{\mathrm{lim}}\left(\sqrt{4{x}^{2}-7x}+2x\right)$

Let x =$-$m
When n → – ∞, then m → ∞.

Dividing the numerator and the denominator by m:

#### Question 24:

$\underset{x\to -\infty }{\mathrm{lim}}\left(\sqrt{{x}^{2}-8x}+x\right)$

$\underset{x\to -\infty }{\mathrm{lim}}\left(\sqrt{{x}^{2}-8x}+x\right)$

Let x = –m

When x → –∞, then m → ∞.

Dividing the numerator and the denominator by m:

#### Question 25:

Evaluate: $\underset{n\to \infty }{\mathrm{lim}}\frac{{1}^{4}+{2}^{4}+{3}^{4}+...+{n}^{4}}{{n}^{5}}-\underset{n\to \infty }{\mathrm{lim}}\frac{{1}^{3}+{2}^{3}+...+{n}^{3}}{{n}^{5}}$

Consider the identity

${\left(k+1\right)}^{5}-{k}^{5}=5{k}^{4}+10{k}^{3}+10{k}^{2}+5k+1$        .....(1)

Putting k = 1, 2, 3,..., n in (1) and then adding the equations, we have

${\left(n+1\right)}^{5}-1=5\sum _{k=1}^{n}{k}^{4}+10\sum _{k=1}^{n}{k}^{3}+10\sum _{k=1}^{n}{k}^{2}+5\sum _{k=1}^{n}k+\sum _{k=1}^{n}1\phantom{\rule{0ex}{0ex}}⇒{n}^{5}+5{n}^{4}+10{n}^{3}+10{n}^{2}+5n=5\sum _{k=1}^{n}{k}^{4}+\frac{10{n}^{2}{\left(n+1\right)}^{2}}{4}+\frac{10n\left(n+1\right)\left(2n+1\right)}{6}+\frac{5n\left(n+1\right)}{2}+n\phantom{\rule{0ex}{0ex}}⇒5\sum _{k=1}^{n}{k}^{4}={n}^{5}+5{n}^{4}+10{n}^{3}+10{n}^{2}+4n-\frac{5{n}^{2}{\left(n+1\right)}^{2}}{2}-\frac{5n\left(n+1\right)\left(2n+1\right)}{3}-\frac{5n\left(n+1\right)}{2}\phantom{\rule{0ex}{0ex}}⇒5\sum _{k=1}^{n}{k}^{4}={n}^{5}+\frac{5{n}^{4}}{2}+\frac{5{n}^{3}}{3}-\frac{n}{6}$

This expression on further simplification gives

$\sum _{k=1}^{n}{k}^{4}=\frac{n\left(n+1\right)\left(2n+1\right)\left(3{n}^{2}+3n-1\right)}{30}$

$=\frac{1}{30}×6-0\phantom{\rule{0ex}{0ex}}=\frac{1}{5}$

#### Question 26:

Evaluate: $\underset{n\to \infty }{\mathrm{lim}}\frac{1.2+2.3+3.4+...+n\left(n+1\right)}{{n}^{3}}$

$\underset{n\to \infty }{\mathrm{lim}}\frac{1.2+2.3+3.4+...+n\left(n+1\right)}{{n}^{3}}\phantom{\rule{0ex}{0ex}}=\underset{n\to \infty }{\mathrm{lim}}\frac{\sum _{k=1}^{n}k\left(k+1\right)}{{n}^{3}}\phantom{\rule{0ex}{0ex}}=\underset{n\to \infty }{\mathrm{lim}}\frac{\sum _{k=1}^{n}{k}^{2}+\sum _{k=1}^{n}k}{{n}^{3}}\phantom{\rule{0ex}{0ex}}=\underset{n\to \infty }{\mathrm{lim}}\frac{\frac{n\left(n+1\right)\left(2n+1\right)}{6}+\frac{n\left(n+1\right)}{2}}{{n}^{3}}$

#### Question 1:

=$\frac{1}{5}\underset{x\to 0}{\mathrm{lim}}\left[\frac{\mathrm{sin}3x}{3x}×3\right]$         $\left[\because \underset{x\to 0}{\mathrm{lim}}\left(\frac{\mathrm{sin}3x}{3x}\right)=1\right]$

$\frac{1}{5}×1×3$

$\frac{3}{5}$

#### Question 2:

We know that $x°=\frac{\mathrm{\pi }}{180}x$.

#### Question 3:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{{x}^{2}}{\mathrm{sin}{x}^{2}}\right]$

Let $\theta ={x}^{2}$

$\underset{\theta \to 0}{\mathrm{lim}}\left(\frac{\theta }{\mathrm{sin}\theta }\right)$

= 1

#### Question 4:

$\frac{1}{3}\underset{x\to 0}{\mathrm{lim}}\left(\frac{\mathrm{sin}x}{x}\right)×\mathrm{cos}x$

$\frac{1}{3}×1×\mathrm{cos}0$

$\frac{1}{3}×1$

= $\frac{1}{3}$

#### Question 5:

$\underset{x\to 0}{\mathrm{lim}}\left[\frac{3\mathrm{sin}x-4{\mathrm{sin}}^{3}x}{x}\right]$

$\left[\because {\mathrm{sin}}^{3}A=3\mathrm{sinA}-4{\mathrm{sin}}^{3}\mathrm{A}\right]$

= 1 × 3

= 3

#### Question 9:

It is of the form $\left(\frac{0}{0}\right)$.

#### Question 10:

It is of the form $\left(\frac{0}{0}\right)$.
Dividing the numerator and the denominator by x:

#### Question 11:

It is of the form $\left(\frac{0}{0}\right)$.

#### Question 19:

Dividing the numerator and the denominator by x, we get:

#### Question 20:

Dividing the numerator and the denominator by x, we get:

#### Question 21:

Dividing the numerator and the denominator by x:

#### Question 25:

Dividing the numerator and the denominator by x:

#### Question 51:

Evaluate the following limits:

$\underset{x\to 0}{\mathrm{lim}}\frac{2\mathrm{sin}x-\mathrm{sin}2x}{{x}^{3}}$

$\underset{x\to 0}{\mathrm{lim}}\frac{2\mathrm{sin}x-\mathrm{sin}2x}{{x}^{3}}\phantom{\rule{0ex}{0ex}}=\underset{x\to 0}{\mathrm{lim}}\frac{2\mathrm{sin}x-2\mathrm{sin}x\mathrm{cos}x}{{x}^{3}}\phantom{\rule{0ex}{0ex}}=\underset{x\to 0}{\mathrm{lim}}\frac{2\mathrm{sin}x\left(1-\mathrm{cos}x\right)}{{x}^{3}}\phantom{\rule{0ex}{0ex}}=\underset{x\to 0}{\mathrm{lim}}\frac{2\mathrm{sin}x×2{\mathrm{sin}}^{2}\frac{x}{2}}{{x}^{3}}$

#### Question 60:

Evaluate the following limits:

$\underset{x\to 0}{\mathrm{lim}}\frac{x\left\{\mathrm{sin}\left(\alpha +\beta \right)x+\mathrm{sin}\left(\alpha -\beta \right)x+\mathrm{sin}2\alpha x\right\}}{{\mathrm{cos}}^{2}\beta x-{\mathrm{cos}}^{2}\alpha x}$

Ans

#### Question 61:

Evaluate the following limits:

$\underset{x\to 0}{\mathrm{lim}}\frac{\mathrm{cos}ax-\mathrm{cos}bx}{\mathrm{cos}cx-1}$

#### Question 62:

Evaluate the following limits:

$\underset{h\to 0}{\mathrm{lim}}\frac{{\left(a+h\right)}^{2}\mathrm{sin}\left(a+h\right)-{a}^{2}\mathrm{sin}a}{h}$

$\underset{h\to 0}{\mathrm{lim}}\frac{{\left(a+h\right)}^{2}\mathrm{sin}\left(a+h\right)-{a}^{2}\mathrm{sin}a}{h}\phantom{\rule{0ex}{0ex}}=\underset{h\to 0}{\mathrm{lim}}\frac{\left({a}^{2}+2ah+{h}^{2}\right)\mathrm{sin}\left(a+h\right)-{a}^{2}\mathrm{sin}a}{h}\phantom{\rule{0ex}{0ex}}=\underset{h\to 0}{\mathrm{lim}}\frac{\left(2ah+{h}^{2}\right)\mathrm{sin}\left(a+h\right)+{a}^{2}\mathrm{sin}\left(a+h\right)-{a}^{2}\mathrm{sin}a}{h}\phantom{\rule{0ex}{0ex}}=\underset{h\to 0}{\mathrm{lim}}\frac{\left(2ah+{h}^{2}\right)\mathrm{sin}\left(a+h\right)}{h}+\underset{h\to 0}{\mathrm{lim}}\frac{{a}^{2}\mathrm{sin}\left(a+h\right)-{a}^{2}\mathrm{sin}a}{h}\phantom{\rule{0ex}{0ex}}=\underset{h\to 0}{\mathrm{lim}}\left(2a+h\right)\mathrm{sin}\left(a+h\right)+{a}^{2}\underset{h\to 0}{\mathrm{lim}}\frac{\mathrm{sin}\left(a+h\right)-\mathrm{sin}a}{h}\phantom{\rule{0ex}{0ex}}$

If  find k.

#### Question 4:

Evaluate the following limits:

$\underset{x\to \frac{\mathrm{\pi }}{3}}{\mathrm{lim}}\frac{\sqrt{1-\mathrm{cos}6x}}{\sqrt{2}\left(\frac{\mathrm{\pi }}{3}-x\right)}$

#### Question 19:

where f(x) = sin 2x

#### Question 23:

$\underset{x\to 1}{\mathrm{lim}}\left[\frac{1-\frac{1}{x}}{\mathrm{sin\pi }\left(x-1\right)}\right]\phantom{\rule{0ex}{0ex}}=\underset{x\to 1}{\mathrm{lim}}\left[\frac{x-1}{x\mathrm{sin\pi }\left(x-1\right)}\right]$

Let y = x – 1
If x → 1, then y → 0.

#### Question 30:

Rationalising the denominator, we get:

#### Question 38:

Evaluate the following limits:

$\underset{x\to \mathrm{\pi }}{\mathrm{lim}}\frac{1-\mathrm{sin}\frac{x}{2}}{\mathrm{cos}\frac{x}{2}\left(\mathrm{cos}\frac{x}{4}-\mathrm{sin}\frac{x}{4}\right)}$                                         [NCERT EXEMPLAR]

$\underset{x\to \mathrm{\pi }}{\mathrm{lim}}\frac{1-\mathrm{sin}\frac{x}{2}}{\mathrm{cos}\frac{x}{2}\left(\mathrm{cos}\frac{x}{4}-\mathrm{sin}\frac{x}{4}\right)}$

Put $x=\mathrm{\pi }+h$

When

$\therefore \underset{x\to \mathrm{\pi }}{\mathrm{lim}}\frac{1-\mathrm{sin}\frac{x}{2}}{\mathrm{cos}\frac{x}{2}\left(\mathrm{cos}\frac{x}{4}-\mathrm{sin}\frac{x}{4}\right)}\phantom{\rule{0ex}{0ex}}=\underset{h\to 0}{\mathrm{lim}}\frac{1-\mathrm{sin}\left(\frac{\mathrm{\pi }+h}{2}\right)}{\mathrm{cos}\left(\frac{\mathrm{\pi }+h}{2}\right)\left[\mathrm{cos}\left(\frac{\mathrm{\pi }+h}{4}\right)-\mathrm{sin}\left(\frac{\mathrm{\pi }+h}{4}\right)\right]}\phantom{\rule{0ex}{0ex}}=\underset{h\to 0}{\mathrm{lim}}\frac{1-\mathrm{sin}\left(\frac{\mathrm{\pi }}{2}+\frac{h}{2}\right)}{\mathrm{cos}\left(\frac{\mathrm{\pi }}{2}+\frac{h}{2}\right)\left[\mathrm{cos}\left(\frac{\mathrm{\pi }}{4}+\frac{h}{4}\right)-\mathrm{sin}\left(\frac{\mathrm{\pi }}{4}+\frac{h}{4}\right)\right]}\phantom{\rule{0ex}{0ex}}=\underset{h\to 0}{\mathrm{lim}}\frac{1-\mathrm{cos}\left(\frac{h}{2}\right)}{-\mathrm{sin}\left(\frac{h}{2}\right)\left[\left(\mathrm{cos}\frac{\mathrm{\pi }}{4}\mathrm{cos}\frac{h}{4}-\mathrm{sin}\frac{\mathrm{\pi }}{4}\mathrm{sin}\frac{h}{4}\right)-\left(\mathrm{sin}\frac{\mathrm{\pi }}{4}\mathrm{cos}\frac{h}{4}+\mathrm{cos}\frac{\mathrm{\pi }}{4}\mathrm{sin}\frac{h}{4}\right)\right]}$

#### Question 5:

Let x = π $-$ h
when x → π, then h → 0

#### Question 1:

Rationalising the denominator, we get:

#### Question 2:

Dividing the numerator and the denominator by x:

Let x = 2 + h

x → 2
h → 0

#### Question 16:

Dividing the numerator and the denominator by x:

x → 0
∴ sin x → 0

Let y=sin x

x → 0
y → 0

#### Question 25:

Dividing the numerator and the denominator by x2:

#### Question 26:

Rationalising the numerator: